Using simulated human comfort matrix to measure urban campus gender-based thermal performances - Chowdhury, Shuva; Chowdhury, Sharmistha; Rezve, Md Fahim Hasan (Frontiers in Built Environment, 2024)
The study proposes incorporating human bodily comfort performance through a simulation method to assess the impact of urban microclimate conditions in an urban campus area. A human comfort performance matrix is used based on PET value and gender’s thermal stress conditions. The investigation serves as a way to evaluate open spaces’ climatic performance quantitatively through energy simulation. The method shows a way to measure urban comfort regarding gender perspectives early in the urban decision-making process. The findings of this research have practical implications for urban decision-makers to use robust simulation tools to optimize open space configurations based on gender’s thermal performances.